Examining the determinants of loan default among microfinance banks’ borrowers in Kano State, Nigeria - Nasiru A. Umar (International Journal of Financial, Accounting, and Management, 2022)
Purpose: The study examines how the personal and business characteristics of micro, small and medium enterprise (MSMEs) borrowers of microfinance banks influence loan default, using Kano State as a case study. Research Methodology: The study employed a survey research method and the sample was drawn through multistage stratified random sampling and comprised 544 beneficiaries of microfinance banks selected from 10 local governments across the state. Data was collected using questionnaires and analyzed using Logit and Probit models with the aid of STATA 13 software. Results: The findings revealed that family size, gender, and business age are significant determinants of loan default. Borrowers’ marital status and age as well as the size and location of business were found to be insignificant in predicting loan default among microfinance MSME borrowers. Limitations: Part of the limitations of this study is the difficulty involved in getting the required information from the sampled microfinance beneficiaries. This research considered only personal and business characteristics of microfinance banks’ borrowers as determinants of loan default in some selected areas of Kano State. Findings in other areas may differ. Contributions: This study contributes to the area of microfinance research by adding more value to the knowledge and literature existing in this field. Managers of microfinance banks will also find the outcome of this research useful as it will assist them in understanding the appropriate strategies to adopt in minimizing the default rate of their clients.